FAKTOR-FAKTOR YANG MEMPENGARUHI OBESITAS PADA ANAK DALAM LITERATUR KONTEMPORER: LITERATURE REVIEW - Fany Septriani; Nadiah Khairunnisa; Resti Rahmadika Akbar; Insil Pendri Hariyani; Mutiara Anissa (Journal of Public Health Science, 2026)
Childhood obesity is a major global public health concern due to its increasing prevalence and long-term health consequences. The World Health Organization (WHO) reports that the prevalence of childhood obesity has risen significantly worldwide over the past decades. Childhood obesity not only affects physical health but also increases the risk of psychological and social problems. An imbalance between energy intake and energy expenditure over time leads to excessive fat accumulation, resulting in overweight and obesity. Body Mass Index (BMI) above normal levels is commonly used to indicate obesity in children. The primary cause of obesity is the accumulation of excess body fat due to excessive energy intake relative to energy needs. Childhood obesity is influenced by multiple factors, including genetic, maternal, nutritional, and socio-economic factors. These factors interact to shape dietary patterns, food choices, and physical activity levels, ultimately contributing to the development of obesity in children.